A Cognitive Interpretation of Data Analysis1. (11th April 2014) - Grolemund, Garrett; Wickham, Hadley
Summary This paper proposes a scientific model to explain the analysis process. We argue that data analysis is primarily a procedure to build understanding, and as such, it dovetails with the cognitive processes of the human mind. Data analysis tasks closely resemble the cognitive process known as sensemaking. We demonstrate how data analysis is a sensemaking task adapted to use quantitative data. This identification highlights a universal structure within data analysis activities and provides a foundation for a theory of data analysis. The competing tensions of cognitive compatibility and scientific rigour create a series of problems that characterise the data analysis process. These problems form a useful organising model for the data analysis task while allowing methods to remain flexible and situation dependent. The insights of this model are especially helpful for consultants, applied statisticians and teachers of data analysis.